Parametric Analysis of a Plain-Fin Compact Heat Exchanger for a Small-Scale Gas Turbine - Can Haşimoğlu; Princely Kolle Epie; Göhkan Coşkun; Hakan Serhad Soyhan (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The influence of the thermal parameters of a Plain-Fin Compact Heat Exchanger on its performance is examined in this paper. The objective of this work is to analyse the effect of the different flow and geometric parameters on the output performance of a plain fin compact heat exchanger (PFCHE) designed to be used on a small-scale gas turbine and how these parameters can be used for the optimisation of PFCHEs.In this work, we examined the effects of the variation of input parameters of a plain-fin compact heat exchanger (fin length, fin height, fin thickness, mass flow rate of air and turbine exhaust gas) on the output performance of the heat exchanger (Overall heat exchanger efficiency, fin heat transfer efficiency and the outlet temperatures). The analytical expressions for the outlet temperatures and heat exchanger efficiencies were derived and analysed. Then the derived model was designed and simulated using CFD codes. Also, from the derived expressions, the performance model of the heat exchanger was programmed for analysis. From the results, it shows that the effectiveness (e-value), fin length, fin height and mass flow rates of the gases influence performance of a plain-fin compact heat exchanger. A 50% reduction in fin height can cause as much as an 18% increase in the fin efficiency of the heat exchanger. While a 50% increase in the effectiveness value can cause as much as a 40% increase in the outlet temperature.